2014
DOI: 10.4330/wjc.v6.i7.630
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lead aVR in acute coronary syndrome

Abstract: The 12-lead electrocardiogram (ECG) is a crucial tool in the diagnosis and risk stratification of acute coronary syndrome (ACS). Unlike other 11 leads, lead aVR has been long neglected until recent years. However, recent investigations have shown that an analysis of ST-segment shift in lead aVR provides useful information on the coronary angiographic anatomy and risk stratification in ACS. ST-segment elevation in lead aVR can be caused by (1) transmural ischemia in the basal part of the interventricular septum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
21
0
4
Order By: Relevance
“…Inversion of T wave in lead aVR manifests as a positive T wave (Dilaveris, Antoniou, Gatzoulis, & Tousoulis, 2017;de Luna et al, 2014). ST segment elevation in lead aVR may occur as a result of global subendomyocardial ischemia, which can be caused by 3VD/LMCA stenosis (Tamura, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inversion of T wave in lead aVR manifests as a positive T wave (Dilaveris, Antoniou, Gatzoulis, & Tousoulis, 2017;de Luna et al, 2014). ST segment elevation in lead aVR may occur as a result of global subendomyocardial ischemia, which can be caused by 3VD/LMCA stenosis (Tamura, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lead aVR as an augmented and unipolar limb lead, once believed to provide no further information except reciprocal information from the lateral limb and precordial leads, is now increasingly being investigated for the changes in different circumstances (Gorgels, Engelen, & Wellens, 2001;Tamura, 2014). While, some recent studies have revealed the value of ST segment changes in lead aVR in NSTEMI patients (Barrabes, Figueras, Moure, Cortadellas, & Soler-Soler, 2003;Misumida et al, 2016;Taglieri et al, 2011;Yan et al, 2007), the prognostic role of a positive T wave in lead aVR is not known in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…When occlusion of the LCX artery more distally, the posterolateral wall will not be involved, and the ST-segment vector will be oriented more inferiorly [25]. Cardiologists should pay more attention to the tracing of lead aVR when interpreting the 12-lead ECG in clinical practice [26]. Thus, when assessing the greater risk area in patients with inferior wall AMI, the clinician should consider the presence of ST segment depression in leads aVR and aVL, which implies a large perfusion area of the left ventricle and the need for aggressive therapeutic strategies to improve myocardial reperfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms explaining why an upright aVRT occurs on the ECG are not identified, it has been suggested that a long left anterior descending artery and multivessel disease, in both cases, along with an ischemically injured myocardium in these areas of the heart, would be expected to make a normally negative T-wave inverted and lead to a flat or positive T-wave [20,21,22,23]. Ayhan et al [22] suggested that a positive T-wave in lead aVR in patients with anterior ST segment elevation myocardial infarction undergoing primary PCI may be caused by multivessel disease, and Joki et al [4] evaluated coronary angiography in incident hemodialysis patients and showed that more than half of the patients had significant CAD; it should be noted that >70% of CAD patients had multivessel disease.…”
Section: Discussionmentioning
confidence: 99%